Genealogi Pemikiran Muhammadiyah Ditinjau Dari Pemikiran Pendidikan Muhammad Abduh Pada Universitas Muhammadiyah Prof. Dr. Hamka - Nabila, Fathiyah Hana; Rosinah, Rosinah; Wahidin, Khaerul; Maulana, Muhammad Azka (Universitas Muhammadiyah Yogyakarta, 2023)
Muhammad Abduh was a 19th century reformer who had brilliant ideas for the revival of Islam in many ways. Muhammad Abduh's education aims to educate the mind and soul and develop education to help students achieve happiness in this world and the hereafter. This research aims to analyze the Genealogy of Muhammadiyah Thought in terms of Muhammad Abduh's Educational Thought. In the aspect of reconstruction of education, curriculum and methods at Prof. Dr. Hamka Muhammadiyah University. This research uses descriptive qualitative research, research that provides a systematic description and description by utilizing qualitative data on the object to be studied and in accordance with existing facts. The results of this study show that Muhammad abduh's genealogy is still embedded in Muhammadiyah education and is mostly implemented in the aspects of curriculum and educational methods.